2010
DOI: 10.1016/j.toxicon.2009.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic cross-reactivity and immunogenicity of Bothrops venoms from snakes of the Amazon region

Abstract: Snakebites are still a critical public health problem in developing countries or isolated areas. In Brazil, the North Region has a high distribution coefficient worsened by the significant number of eventually unreported cases, due to difficulties in access to health services, to the natural geographic barriers and the vast territory. In the Rio Negro area, the species Bothrops atrox, Bothrops brazili, Lachesis muta muta and Bothriopsis taeniata are thought to be the major species responsible for snakebites. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…Some of these proteins are of importance to the individual snake in the context of its environment and selective pressures. Furthermore, the species possesses and preserves characteristics that, at some moment during its evolution, are or were essential for survival [48]. Snake venoms contain proteins belonging to several structural classes, such as peptides without enzymatic activity, small neurotoxins, phospholipases A 2 and a number of enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these proteins are of importance to the individual snake in the context of its environment and selective pressures. Furthermore, the species possesses and preserves characteristics that, at some moment during its evolution, are or were essential for survival [48]. Snake venoms contain proteins belonging to several structural classes, such as peptides without enzymatic activity, small neurotoxins, phospholipases A 2 and a number of enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…atrox venom [9,10], but other studies have shown that the Bothrops antivenom can neutralize the toxins of this venom [1114]. All these studies were performed using a prior incubation of the venom with the antivenom, which does not represent the actual situation where the treatment with antivenom follows the envenomation after the onset of the primary venom-induced effects.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we evaluated the PLA 2, proteolytic, and LAAO activities of the venoms of five different Bothrops species: B. jararaca, B. jararacussu, B. moojeni, B. neuwiedi, and B. alternatus. Such enzymatic variations are highly relevant, given that the venom of these species is used in the production of bothropic antivenom in Brazil (Furtado et al, 2010). It is noteworthy that, with the exception of B. neuwiedi, all of the snakes evaluated are on the list of venomous snakes of highest medical significance in the Americas (World Health Organization, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, some researchers consider the groups B. microphtalmus and B. taeniatus to be members of the Bothrocophias and Bothriopsis genera, respectively (Campbell and Lamar, 2004;Gutberlet and Campbell, 2001). The species Bothrops moojeni belongs to the B. atrox group, together with the species Bothrops asper; Bothrops leucurus and Bothrops marajoensis (Furtado et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation